Inside Back Cover: Vancomycin Resistance Is Overcome by Conjugation of Polycationic Peptides (Angew. Chem. Int. Ed. 23/2020). Issue 23 (15th April 2020) - Umstätter, Florian; Domhan, Cornelius; Hertlein, Tobias; Ohlsen, Knut; Mühlberg, Eric; Kleist, Christian; Zimmermann, Stefan; Beijer, Barbro; Klika, Karel D.; Haberkorn, Uwe; Mier, Walter; Uhl, Philipp
Abstract : Bacterial resistance threatens to destroy the achievements of antibiotic therapy. As P. Uhl and co‐workers report in their Communication on page 8823, a 1000‐fold increase in the activity of the reserve antibiotic vancomycin was achieved by using peptide conjugates. This approach reveals the potential of chemically modifying proven natural products as an alternative to the costly de novo development of active substances.